2012
DOI: 10.1016/j.cortex.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Learning to associate novel words with motor actions: Language-induced motor activity following short training

Abstract: Action words referring to face, arm or leg actions activate areas along the motor strip that also control the planning and execution of the actions specified by the words. This electroencephalogram (EEG) study aimed to test the learning profile of this language-induced motor activity. Participants were trained to associate novel verbal stimuli to videos of object-oriented hand and arm movements or animated visual images on two consecutive days. Each training session was preceded and followed by a test-session … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
47
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 46 publications
11
47
1
2
Order By: Relevance
“…Despite a possible role for alpha oscillations in embodied language processing (van Elk et al, 2010;Fargier et al, 2012), no clusters in the alpha range were identified in the comparison between conditions nor were suggested by alpha power topographies. This indicates that oscillations in the beta band are the specific neurophysiological mechanism associated with language-motor interference.…”
Section: Meg Power Modulations and Semantic Interferencementioning
confidence: 61%
See 1 more Smart Citation
“…Despite a possible role for alpha oscillations in embodied language processing (van Elk et al, 2010;Fargier et al, 2012), no clusters in the alpha range were identified in the comparison between conditions nor were suggested by alpha power topographies. This indicates that oscillations in the beta band are the specific neurophysiological mechanism associated with language-motor interference.…”
Section: Meg Power Modulations and Semantic Interferencementioning
confidence: 61%
“…Taken together, the role of beta oscillations in embodied language processing makes it a feasible candidate for a functional mechanism of language-motor interference. Similarly, alpha band (8-13 Hz) oscillations have been associated with action execution (Salmelin et al, 1995;Sebastiani et al, 2014), observation (Caetano et al, 2007;Avanzini et al, 2012), motor imagery (Pfurtscheller et al, 2006;de Lange et al, 2008), spoken language processing (Strauß et al, 2014), and action language processing (Alemanno et al, 2012;Fargier et al, 2012). Since alpha band oscillations may be more related to sensory than motor processing (Salmelin et al, 1995;Brinkman et al, 2014;Sebastiani et al, 2014;Coll et al, 2015), the focus in the current study is on the beta band, but alpha oscillations are also investigated.…”
Section: Introductionmentioning
confidence: 92%
“…One drawback of the study, however, is that the absence of non-action sentences as a contrasting condition does not allow the conclusion that these timeresolved mu and beta rhythms are exclusively modulated by action language. A different research strategy was employed by Fargier et al (2012). They trained participants to associate new words with action related videos or with visual motion videos in two sessions.…”
Section: Introductionmentioning
confidence: 99%
“…Further, b-oscillations are very sensitive towards dissociation between concrete and abstract concepts (Weiss & Müller, 2013;Weiss & Rappelsberger, 1996. Recently, in the context of the embodied language theory, studies revealed that power decreases in the b-as well as the l-band are correlated with the processing of concrete action related language (Alemanno et al, 2012;Fargier et al, 2012;Moreno, de Vega, & León, 2013;Moreno et al, 2015;van Elk, van Schie, Zwaan, & Bekkering, 2010). This finding strongly sup-ports the theory of embodiment, which, in the case of language processing, indicates that understanding linguistic input requires a mental neural simulation of respective sensorimotor information in somatosensory and motor areas (Barsalou, 1999(Barsalou, , 2008Gallese & Lakoff, 2005;Glenberg & Kaschak, 2003; for a review see also Buccino, Colagè, Gobbi, & Bonaccorso, 2016).…”
Section: Introductionmentioning
confidence: 99%